Composite Physical - Mechanical Properties Of Bazalt Reinforcement And Comparison With Steel Reinforcement And Inspection For Flammability (Texas Journal of Engineering and Technology, 2024)
This article discusses the effectiveness and scope of steel and composite reinforcement, their advantages and disadvantages, as well as a comparison of their main characteristics. Describes tests to determine the combustibility of basalt reinforcement, in order to determine the possibilities of its application.